Incursion of non-professionals into property management practice in Nigeria - Tunde Oladokun, Timothy; Ojo, Olatoye (Property management, 2011)
Purpose - The paper seeks to identify the factors that are responsible for the incursion of non-professionals, otherwise called quacks, into property management practice in Nigeria.Design methodology approach - Primary data were collected with the aid of questionnaires served on 270 estate surveying firms based in the study area. The proportion method was used to determine the factors that are significantly responsible for the daily incursion of non-professionals whose activities have negatively affected real estate investment in the country.Findings - The result shows that the high income derivable from property management practice is a major factor. Other factors in their perceived order of importance include provision of unsatisfactory and less than standard service by estate surveyors, lack of confidence by clients on the estate surveyor to evict erring tenants and shortage of qualified personnel.Research limitations implications - Obtaining the perception of practitioners could subject the findings of the study to bias. Further research targeted at the clients of property management services will provide a balanced view.Originality value - The findings from this study will provide professional bodies and policy makers with data to curb the activities of quacks and enhance the practice of real estate management.